2021
DOI: 10.1097/mcg.0000000000001495
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fecal Microbiota Transplant Capsules Are Safe and Effective for Recurrent Clostridioides difficile Infection

Abstract: Goals: We performed a systematic review with meta-analysis to examine the efficacy and safety of oral fecal microbiota transplantation (FMT) capsules for recurrent Clostridioides difficile infection (rCDI). Background: FMT through colonoscopy is established as effective and safe in treating multiple recurrences of CDI, but consensus has not been established on delivery through oral capsules. Study: A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…45 The cure rates in the five included studies using lyophilised faecal material were comparable to the other studies, which has also been previously reported. 23,42,44,49,50,52 The introduction of encapsulated FMT with lyophilised faeces will only reinforce the applicability of the treatment since it can be administered with fewer capsules to swallow and potentially storage in the patients' refrigerator or freezer in case of treatment regimens of more than one day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The cure rates in the five included studies using lyophilised faecal material were comparable to the other studies, which has also been previously reported. 23,42,44,49,50,52 The introduction of encapsulated FMT with lyophilised faeces will only reinforce the applicability of the treatment since it can be administered with fewer capsules to swallow and potentially storage in the patients' refrigerator or freezer in case of treatment regimens of more than one day.…”
Section: Discussionmentioning
confidence: 99%
“…FMT treatment is generally considered safe when donor-screening protocols are followed. 23,27,[86][87][88] No cases of transferred diseases were reported in any of the studies included in this review and only a few serious adverse events, mostly considered not related to treatment, were reported. Encapsulated FMT did not introduce more adverse events than FMT through other routes, but it may possibly introduce more than placebo when administered long term, as reported by Halkjaer and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…There has been a shift in recent years in the modes of delivery of FMT from oesophagogastroduodenoscopy, nasogastric/jejunal/duodenal tubes, colonoscopy, Open access retention enema to oral capsule. [37][38][39] However, patients' perspective in using FMT as a treatment modality remains to be further studied to identify the factors that improve attitudes and practices. In our study, more than half of the population were unlikely to take faecal pills, to treat diarrhoea.…”
Section: Probioticsmentioning
confidence: 99%